The Prevalence of Diabetes Mellitus in Chronic Obstructive Pulmonary Disease Patients - Mariska Pangaribuan; Faisal Yunus; Triya Damayanti; Rochsismandoko Rochsismandoko (Jurnal Respirologi Indonesia, 2020)
Backgrounds: Type 2 diabetes mellitus (DM) is a common comorbidity of COPD. COPD may be considered as a risk factor for new onset type 2 DM via multiple pathophysiological alterations such as systemic inflammation, smoking, oxidative stress, obesity and inhaled corticosteroid use. Exact prevalence of DM in COPD patients in Indonesia still unclear. Co-morbid conditions like DM have great impact on the outcome of COPD in the form of severity, morbidity and mortality. Methods: A cross sectional study was done in Asthma-COPD clinic Persahabatan Hospital from February to March 2017 to screen COPD patients for DM. Sixty-four subjects were recruited. Interview, physical examination and laboratory testing were performed in all subjects. Results: A total of 64 patients with COPD (Males=60, Female=4) with mean age 65±8.7 were screened for DM. Patients with known history of DM were 12 subjects (18.8%) and were enrolled as known DM cases. Remaining 52 subjects (81.3%) whose DM status was unclear were screened by random or fasting blood sugar and HbA1c. Two subjects (3.1%) were considered as newly diagnosed DM cases. Prevalence of DM in present study was 21.9%. Number of patients with pre-diabetes was 16 subjects (25%). There was no significant relationship between gender, age, smoking, nutritional status, airflow limitation and inhaled corticosteroid use in occurrence of DM among COPD patients. Conclusions: Prevalence of DM in COPD patients in the present study is 21.9%. It is important to screen all COPD patients for DM routinely. (J Respir Indo. 2020; 40(1): 48-57)